Acetaminophen Use and Risk of Asthma, Rhinoconjunctivitis, and Eczema in Adolescents: International Study of Asthma and Allergies in Childhood Phase Three - Mallol-Villablanca, E (American Thoracic Society, 2011)
Rationale: There is epidemiological evidence that the use of acetaminophen may increase the risk of developing asthma. Objectives: To investigate the risk of asthma and other allergic disorders associated with the current use of acetaminophen in 13- to 14-year-old children in different populations worldwide. Methods:As part of the International Study ofAsthmaandAllergies in Childhood (ISAAC) Phase Three, 13- to 14-year-old children completed written and video questionnaires obtaining data on current symptoms of asthma, rhinoconjunctivitis, and eczema, and a written environmental questionnaire obtaining dataon putative risk factors, including acetaminophen use in the past 12 months. Measurements and Main Results: The primary outcome measure was the odds ratio (OR) of current asthma symptoms associated with acetaminophen use calculated by logistic regression. A total of 322,959 adolescent children from 113 centers in 50 countries participated. In the multivariate analyses the recent use of acetaminophen was associated with an exposure-dependent increased risk of current asthmasymptoms(OR, 1.43 [95%confidenceinterval, 1.33-1.53] and 2.51 [95% confidence interval, 2.33-2.70] for medium and high versus no use, respectively). Acetaminophen use was also associated with an exposure-dependent increased risk of current symptoms of rhinoconjunctivitis and eczema. Conclusions: Acetaminophen use may represent an important risk factor for the development and/or maintenance of asthma, rhinoconjunctivitis, and eczema in adolescent children.
Keywords: Acetaminophen; Asthma; Eczema; ISAAC; Rhinoconjunctivitis